1976
DOI: 10.1139/v76-167
|View full text |Cite
|
Sign up to set email alerts
|

Reaction rates of electrons in liquid methanol and ethanol: effects of pressure

Abstract: The value of the rate constant kl for the reaction e-s,lv + RO-s,lv + H, [I], at 295 K and 1 bar is 51.4 X lo5 s-1 in methanol and 5 8 X 104 s-1 in ethanol. The respective volumes of activation averaged between 1 bar and 2 kbar are AVl* 2 -21 and 5 -22 cm3 mol-1. A high concentration of potassium hydroxide (1 M) or water (5 M) decreases the apparent value of kl somewhat but has little or no effect on the value of AV,". The effect of pressure on the rate constant of e-s,lv + S + product, [2], was also measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Electron capture by toluene, and probably by allyl alcohol, is stabilized by protonation (26,27): [4] S-, + ROH + i~ + RO-, Reaction [4] involves the rotation of solvent dipoles adjacent to the reaction site as the charge center changes from S-to RO-; the reaction rate should correlate with the dielectric relaxation For personal use only. (14,15).…”
Section: Oooit (K)mentioning
confidence: 99%
“…Electron capture by toluene, and probably by allyl alcohol, is stabilized by protonation (26,27): [4] S-, + ROH + i~ + RO-, Reaction [4] involves the rotation of solvent dipoles adjacent to the reaction site as the charge center changes from S-to RO-; the reaction rate should correlate with the dielectric relaxation For personal use only. (14,15).…”
Section: Oooit (K)mentioning
confidence: 99%
“…Possible exceptions are e; + ROH + H + RO; and e; + ROH;, + H + ROH in water and alcohols, where a proton from a solvating -OH or -OH; group might transfer to the site of the electron (3). Proton transfer to the "cavity" of the electron site might avoid the work needed to create a new site for the H atom if the electron were to transfer first, followed by decomposition of the transient ROH-or ROH2.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused our attention on (i) the prevailing trajectory of IR prehydrated electrons, and (ii) the role of early branchings between reactive (eq 1a) and nonreactive (eq 1b) channels. Due to the low C 37 value of aqueous Cd 2+ , the computed kinetic model investigates a prehydration one-electron reduction of Cd 2+ . This ultrafast redox channel would be triggered by an electron photodetachment from excited aqueous chloride ions with a probability P Reac (eq 3).…”
Section: Resultsmentioning
confidence: 99%
“…In polar solutions, intermolecular electron transfer faster than the picosecond solvation process has been investigated by fluorescence up-conversion but up to now competitive nonreactive electron dynamics (electron solvation) and ultrafast presolvation radical reactions in water have not be investigated at very short times. Nanosecond and picosecond pulse radiolysis studies have suggested that ultrafast radical reaction (univalent reduction of a solute) would involve hot electrons or short-lived precursors of hydrated electron. These indirect investigations determine the subnanosecond G value of solvated electrons for different electron scavenger concentrations. The pulse radiolysis experiments treat the data by determining empirical relationships between the rate constant of an electron transfer and the C 37 value, or stochastic analysis of competitive electron solvation and electron capture .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation